How anterior pelvic tilt affects the lower extremity kinematics during the late swing phase in soccer players while running: A time series analysis - Alizadeh, S.; Mattes, K. (Human Movement Science, 2019)
Anterior pelvic tilt has been proposed to predispose the hamstring in soccer players to injury at the late swing phase during a sprint, however the mechanism on how the changes in the alignment would affect the kinematics are still unclear. Thirty-four male amateur soccer players were recruited for this study. Pelvic tilt was measured using the DIERS Formetric 4D. Lower extremity angles were recorded using an 8-camera Vicon motion capture system at 200 Hz while the athlete performed a high speed run on a motorised treadmill. Late swing phase was extracted from 5 running cycle which were later analysed using statistical parametric mapping (SPM). The results show that the increase of anterior pelvic tilt angle was significantly correlated with hip (r = -0.421 to -0.462, p = 0.015) and knee flexion (r = -0.424 to -0.472, p = 0.026) values. No other correlation was found between the anterior pelvic tilt and the angles at the coronal plane. By using time series analysis it was shown that the anterior pelvic tilt measured in a standing position would affect the adjacent segments` kinematics while running as suggested in the kinetic chain theory; which would potentially predispose the soccer athletes to hamstring injury by maintaining knee extension.